Embryonic encapsulated development of the gastropod Acanthina monodon is impacted by future environmental changes of temperature and pCO2. (May 2023) - Paredes-Molina, F.J.; Chaparro, O.R.; Navarro, J.M.; Cubillos, V.M.; Montory, J.A.; Pechenik, J.A.
Abstract: Egg capsules of the gastropod Acanthina monodon were maintained during the entire period of encapsulated development at three temperatures (10, 15, 20 °C) and two pCO2 levels (400, 1200 μatm). Embryos per capsule, size at hatching, time to hatching, embryonic metabolic rates, and the resistance of juveniles to shell breakage were quantified. No embryos maintained at 20 °C developed to hatching. The combination of temperature and pCO2 levels had synergistic effects on hatching time and developmental success, antagonistic effects on number of hatchlings per capsule, resistance to juvenile shell cracking and metabolism, and additive effect on hatching size. Juveniles hatched significantly sooner at 15 °C, independent of the pCO2 level that they had been exposed to, while individuals hatched at significantly smaller sizes if they had been held under 15 °C/1200 μatm rather than at 10 °C/low pCO2 . Embryos held at the higher pCO2 had a significantly greater percentage of abnormalities. For capsules maintained at low pCO2 and 15 °C, emerging juveniles had less resistance to shell breakage. Embryonic metabolism was significantly higher at 15 °C than at 10 °C, independent of pCO2 level. The lower metabolism occurred in embryos maintained at the higher pCO2 level. Thus, in this study, temperature was the factor that had the greatest effect on the encapsulated development of A. monodon, increasing the metabolism of the embryos and consequently accelerating development, which was expressed in a shorter intracapsular development time, but with smaller individuals at hatching and a lower resistance of their shells to breakage. On the other hand, the high pCO2 level suppressed metabolism, prolonged intracapsular development, and promoted more incomplete development of the embryos. However, the combination of the two factors can mitigate--to some extent--the adverse effects of both incomplete development and lower resistance to shell breakage. Graphical abstract: Image 1 Highlights: Development of encapsulated embryos is accelerated by temperature and slowdown by pCO2 . Combination of temperature and pCO2 negatively impact juvenile hatching size. Increased pCO2 negatively impacts the correct embryo's development. Increased temperature mitigates the negative effects of pCO2 on hatchlings shell quality. Embryos metabolism increase with increasing temperature and decrease with increasing pCO2 .